HUBUNGAN FAKTOR PREDISPOSISI DENGAN KETERLAMBATAN BEROBAT PASIEN KANKER PAYUDARA LANJUT LOKAL - Juliana, Adies; Budiwinata, Winardi; Oktaviyanti, Ika Kustiyah (Homeostasis, 2024)
Abstract: Breast cancer patients often come to the doctor diagnosed at a locally advanced stage. The cause of delay in treatment is influenced by predisposing factors, namely knowledge, family history, education level, attitude, action to seek health facilities, fear, and family income. The study aimed to analyze the relationship between predisposing factors and the delay in treatment of locally advanced breast cancer patients. The study used an analytic observational method with a cross sectional approach. The study respondents were 51 patients with locally advanced breast cancer who sought treatment at the Oncology Surgery Polyclinic and were recorded in the medical records of RSUD Ulin Banjarmasin for the period January 2020-November 2023. Data were collected based on a questionnaire of predisposing factors for delay in treatment. Data analysis used Fisher's test on SPSS and was said to have a significant relationship if p < 0.05. As a result, the majority of respondents were in the inoperable category 96.1% with poor knowledge (84.3%; p=0.022), low education level (51%; p=1), no family history (56.9%; p=0.5), poor attitude (92.2%; p=0.152), poor action to seek health facilities (90.2%; p=0.188), fear of symptoms (82.4%; p=0.152), and low family income (60.8%; p=1). In conclusion, there was a significant association between knowledge and delay in seeking treatment for locally advanced breast cancer patients. Meanwhile, the level of education, family history, attitude, action to seek health facilities, fear and family income did not have a significant relationship with the delay in treatment of locally advanced breast cancer patients. Keywords: breast cancer, locally advanced, predisposing factor, treatment delay Abstrak: Pasien kanker payudara seringkali datang ke dokter terdiagnosis pada stadium lanjut lokal. Penyebab keterlambatan berobat tersebut dipengaruhi oleh faktor predisposisi, yaitu pengetahuan, riwayat keluarga, tingkat pendidikan, sikap, tindakan mencari fasilitas kesehatan, rasa takut, dan penghasilan keluarga. Penelitian bertujuan menganalisis hubungan faktor predisposisi dengan keterlambatan berobat pasien kanker payudara lanjut lokal. Penelitian menggunakan metode observasional analitik dengan pendekatan cross sectional. Responden penelitian adalah 51 pasien kanker payudara lanjut lokal yang berobat ke Poliklinik Bedah Onkologi dan terdata di rekam medis RSUD Ulin Banjarmasin periode Januari 2020-November 2023. Data dikumpulkan berdasarkan kuesioner dan analisis data menggunakan uji Fisher pada SPSS, dikatakan memiliki hubungan signifikan apabila p < 0,05. Hasilnya, mayoritas responden dalam kategori inoperable 96,1% dengan pengetahuan kurang (84,3%; p=0,022) tingkat pendidikan rendah (51%; p=1), tidak memiliki riwayat keluarga (56,9%; p=0,5), sikap kurang (92,2%; p=0,152), tindakan mencari fasilitas kesehatan kurang (90,2%; p=0,188), takut gejala (82,4%; p=0,152), dan penghasilan keluarga rendah (60,8%; p=1). Kesimpulannya, terdapat hubungan signifikan antara pengetahuan dengan keterlambatan berobat pasien kanker payudara lanjut lokal. Aspek tingkat pendidikan, riwayat keluarga, sikap, tindakan mencari fasilitas kesehatan, rasa takut dan penghasilan keluarga tidak terdapat hubungan signifikan dengan keterlambatan berobat pasien kanker payudara lanjut lokal. Kata-kata kunci: kanker payudara, stadium lanjut lokal, faktor predisposisi, keterlambatan berobat